KHUSYŪ‘ DALAM AL-QUR’AN (STUDI ANALISIS TAFSIR AL JĀMI‘ LI AHKĀM AL-QUR’AN) - Fatimah, Salma Ultum; Hidayat, M. Riyan (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
This research focuses on the concept of khusyu' contained in Tafsir Al Jāmi' Li Ahkām Al-Qur'an written by Imam Al-Qurtubi in depth and comprehensively. The method used is descriptive analytical. This research is based on a literature review using various books in the library and digitally that can be accessed easily. The results of this study indicate that khusyu' interpreted by Al-Qurtubi can be implemented into various activities such as Gaining peace of mind, Strengthening soul and mentality, Always remembering the hereafter, Avoiding a hard heart, Gaining an attitude of Tawadhu' to God as well as to others, Gaining Attitude Tawadhu 'to Allah as well as to others, and Leads to luck and success in life.